Importance of studies on aging processes of animals in the search for means to prolong human life - ΧΑΤΖΗΟΛΟΣ Β. (Journal of the Hellenic Veterinary Medical Society, 2019)
The aging process is a fundamental mystery and one of the most complex biological problems facing scientists today. A fascination with longevity and the quest for eternal youth has prompted man, throughout history, to seek methods to halt the effects of aging. That the potential for prolonged human life exists is evident from records of physical activity and mental alertness of aged individuals. While the underlying basis for these exceptional life spans remains unknown, scientists have delved into the aging processes to gain the needed knowledge. Because experimentation with humans is limited, researchers have turned to cell culture techniques (in vitro and in vivo) and to manipulation of those wild and domestic animals which provide excellent models for human systems. Veterinarians have worked closely whith the National Institute of Aging (NIA) to develop a large and varied reservoir of cellular and live animal material for research on aging. Apart from basic knowledge in determining the life span of certain species and the establishment of criteria for age diagnosis, the new technique of racemization is mentioned for potential use in aging studies. In addition, reference is made to changes in the organs (liver, kidney, gonads, etc) which occur over the aging process. The aging process is a fundamental mystery and one of the most complex biological problems facing scientists today. A fascination with longevity and the quest for eternal youth has prompted man, throughout history, to seek methods to halt the effects of aging. That the potential for prolonged human life exists is evident from records of physical activity and mental alertness of aged individuals. While the underlying basis for these exceptional life spans remains unknown, scientists have delved into the aging processes to gain the needed knowledge. Because experimentation with humans is limited, researchers have turned to cell culture techniques (in vitro and in vivo) and to manipulation of those wild and domestic animals which provide excellent models for human systems. Veterinarians have worked closely whith the National Institute of Aging (NIA) to develop a large and varied reservoir of cellular and live animal material for research on aging. Apart from basic knowledge in determining the life span of certain species and the establishment of criteria for age diagnosis, the new technique of racemization is mentioned for potential use in aging studies. In addition, reference is made to changes in the organs (liver, kidney, gonads, etc) which occur over the aging process.